Designing educational environment for the training of managers of industrial sphere - Margarita V. Gorshenina; Elena J. Firsova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The concepts of "educational space", "educational environment" are important characteristics of the educational process. A necessary condition for the preparation of competitive specialists now becomes the integration of professional and educational environments. In this work, professionally oriented educational environment is considered as a set of pedagogical conditions and means of learning, contributing to the formation of readiness of managers of industrial areas to the profession. The system of formation of readiness for professional work of managers of industrial sphere in the conditions of professionally oriented educational environment.